Shear testing of URM wallettes retrofitted with NSM steel wire rope. (October 2020) - Misnon, Noor Aina; Giaretton, Marta; Shedde, Devina; Ingham, Jason; Dizhur, Dmytro
Abstract: An experimental program was undertaken with the aim of investigating the in-plane behaviour of unreinforced clay-brick masonry (URM) wallettes retrofitted using the near surface mounted steel wire rope (NSM-SWR) method. A total of ten double-leaf URM wallettes, each with dimensions of 1200 mm × 1200 mm × 235 mm, were tested in induced diagonal shear. One wallette was tested in the as-built condition and was used as a benchmark to define the performance of the nine wallettes that were retrofitted with different configurations of lengths of NSM-SWR. Two-part epoxy and cement grout were used as adhesives to provide coupling between the wire rope and the clay-brick masonry. Several parameters affecting the shear behaviour of the retrofitted URM wallettes were investigated, including the failure mode, shear strength, maximum drift and pseudo-ductility, with the results and associated analysis presented herein.